MODEL-BASED ANALYSIS OF THE EFFECTS OF RECYCLE RATIOS ON THE PERFORMANCE OF AN A2O PROCESS - Manav Demir, Neslihan; Demir, Selami (YILDIZ TECHNICAL UNIV, 2020)
This study presents findings of a modeling work in which the effects of internal recycle (IR) and return activated sludge (RAS) ratios on the treatment performance of an A(2)O process were investigated. Simulations were performed using activated sludge model no.3 extended with biological phosphorus removal processes at an influent wastewater temperature of 20 degrees C. The results showed that not only IR ratio but also RAS ratio affects both nitrogen and phosphorus removal processes. The removal efficiencies for total nitrogen (TN) and total phosphorus (TP) changed between 71%-83% and 53%-80%, respectively, at different IR and RAS ratios. On the other hand, chemical oxygen demand (COD), total Kjeldahl Nitrogen (TKN), and total suspended solids (TSS) removal efficiencies stayed relatively constant at around 90%, 96%, and 93%, respectively, with varying IR and RAS ratios. Results indicated that an optimum set of IR and RAS ratios can be found out by activated sludge modeling. For A(2)O process, an IR ratio of 2.5 to 3.5 at a RAS ratio of 0.75 to 0.90 offer the best performance in terms of both TN and TP removal efficiencies.
Keywords: A(2)O process; internal recycle; return activated sludge; activated sludge modeling; MUNICIPAL WASTE-WATER; PHOSPHORUS REMOVAL; ACTIVATED-SLUDGE; NITROGEN REMOVAL; TREATMENT-PLANT; SYSTEM; Engineering